Sedimentary record of Jurassic northward subduction of the Bangong–Nujiang Ocean: insights from detrital zircons. Issue 2 (25th January 2017) - Huang, Tong-Tong; Xu, Ji-Feng; Chen, Jian-Lin; Wu, Jian-bin; Zeng, Yun-Chuan
ABSTRACT: The subduction polarity and related arc–magmatic evolutional history of the Bangong–Nujiang Ocean, which separated the South Qiangtang terrane to the north from the North Lhasa terrane to the south during the Mesozoic, remain debated. This study tries to reconstruct the subduction and evolution of the Bangong–Nujiang Ocean on the basis of U–Pb and Hf isotopic analyses of detrital zircons in samples from sedimentary rocks of the middle-western section of the Bangong–Nujiang suture zone in Gerze County, central Tibet. The Middle Jurassic Muggargangri Group in the Bangong–Nujiang suture zone was deposited in a deep-sea basin setting on an active continental margin. The Late Jurassic strata, such as the Sewa Formation, are widely distributed in the South Qiangtang terrane and represent deposition on a shelf. The Early Cretaceous Shamuluo Formation in the Bangong–Nujiang suture zone unconformably overlies the Muggargangri Group and was probably deposited in a residual marine basin setting. The detrital zircons of the Muggargangri Group contain seven U–Pb age populations: 2.6–2.4 Ga, 1.95–1.75 Ga, 950–900 Ma, 850–800 Ma, 650–550 Ma, 480–420 Ma, and 350–250 Ma, which is similar to the age populations in sedimentary rocks of the South Qiangtang terrane. In addition, the age spectra of the Shamuluo Formation are similar to those of the Muggargangri Group, indicating that both had a northern terrane provenance, which is conformed by the north-to-south palaeocurrent. This provenance indicates northward subduction of the Bangong–Nujiang oceanic crust. In contrast, two samples from the Sewa Formation yield variable age distributions: the lower sample has age populations similar to those of the South Qiangtang terrane, whereas the upper possesses only one age cluster with a peak at ca. 156 Ma. Moreover, the majority of the late Mesozoic detrital zircons are characterized by weakly positive εHf(t) values that are similar to those of magmatic zircons from arc magmatic rocks in the South Qiangtang terrane. The findings, together with information from the record of magmatism, indicate that the earliest prevalent arc magmatism occurred during the Early Jurassic (ca. 185 Ma) and that the principal arc–magmatic stage occurred during the Middle–Late Jurassic (ca. 170–150 Ma). The magmatic gap and scarcity of detrital zircons at ca. 140–130 Ma likely indicate collision between the Qiangtang and Lhasa terranes. The late Early Cretaceous (ca. 125–100 Ma) magmatism on both sides of the Bangong–Nujiang suture zone was probably related to slab break-off or lithospheric delamination after closure of the Bangong–Nujiang Ocean.